2022
DOI: 10.3389/fpsyg.2022.940977
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and systematic review of physical activity on neurodevelopment disorders, depression, and obesity among children and adolescents

Abstract: BackgroundNo consensus on whether physical activity (PA) is related to physical and mental health among pediatric population remains has been reached to date. To further explore their association, our study assessed the effect of PA on physical and mental health of children and adolescents through a systematic review and meta-analysis of randomized controlled studies (RCTs).MethodsSeveral databases(Web of science, PubMed, Embase, Cochrane Central register of controlled trials, CINAHL) were searched from incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Systematic review studies have found positive effects of physical activity interventions on mental health in different age groups. Peng et al reported that the administration of a physical activity intervention may lead to moderate improvements in symptoms of depression in adolescents aged 12–18 years old [ 10 ]. In addition, Hale et al summarized studies involving physical activity interventions for children aged 6 to 11 years old and concluded that these interventions had positive effects on mental health in school and neighborhood settings, but evidence on reducing ill-being in children remained unclear [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic review studies have found positive effects of physical activity interventions on mental health in different age groups. Peng et al reported that the administration of a physical activity intervention may lead to moderate improvements in symptoms of depression in adolescents aged 12–18 years old [ 10 ]. In addition, Hale et al summarized studies involving physical activity interventions for children aged 6 to 11 years old and concluded that these interventions had positive effects on mental health in school and neighborhood settings, but evidence on reducing ill-being in children remained unclear [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, moderate to high-intensity Physical Activity have a substantial effect in reducing depressive symptoms and enhancing life satisfaction ( Marconcin et al, 2022 ). Another meta-analysis further supports this view, noting a significant positive correlation between the frequency and intensity of physical activity and the extent of improvement in psychological health ( Peng et al, 2022 ). In summary, regular participation in Physical Activity can significantly enhance the psychological health of adolescents, with higher frequencies and intensities of Activity leading to better outcomes.…”
Section: Resultsmentioning
confidence: 82%
“…By comparing data before and after interventions, many studies consistently find that Physical Activity improve adolescents’ psychological states, reducing negative emotions such as depression and anxiety, and enhancing overall psychological well-being. Furthermore, the frequency and intensity of participation in Physical Activity are positively correlated with the degree of improvement in psychological health ( Pascoe et al, 2020 ; Marconcin et al, 2022 ; Peng et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In another crosssectional study, Gafni et al (2022) found that insufficient PA and sitting for at least three-quarters of the day increased the risk of MCI in the elderly. In other words, low PA and prolonged SB adversely affect cognitive function in the elderly (Peng et al, 2022). This could be due to the high prevalence of chronic inflammation and reduced hormone levels associated with older stages of life.…”
Section: Discussionmentioning
confidence: 99%